2020
DOI: 10.1007/s11332-020-00719-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between children physical activity, inflammatory mediators and lymphocyte activation: possible impact of social isolation (COVID-19)

Abstract: Objective Lifestyle and body composition may be simultaneously responsible for immune response modulation. This study aimed to compare plasmatic adipokines concentration and lymphocyte cytokine production in children with different daily steps (DS) range, as well as to discuss the potential negative impact of the social isolation during COVID-19 pandemic in this context. DS can be a useful and low-cost way of monitoring children's health status. Study design Fifty children were classified into clusters based i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…73 , 92 Two studies designed and validated new questionnaires for children in lockdown, 93 , 94 and 3 studies used device-based measures of PA, including accelerometry 73 and pedometry. 95 , 96 Four studies used qualitative approaches, including interviews, 97 parent-to-child interviews, 98 open-ended questions, 92 and a case study. 99 The remaining studies relied on nonvalidated measures of PA through self-reported questionnaires constructed by the researchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…73 , 92 Two studies designed and validated new questionnaires for children in lockdown, 93 , 94 and 3 studies used device-based measures of PA, including accelerometry 73 and pedometry. 95 , 96 Four studies used qualitative approaches, including interviews, 97 parent-to-child interviews, 98 open-ended questions, 92 and a case study. 99 The remaining studies relied on nonvalidated measures of PA through self-reported questionnaires constructed by the researchers.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 73 , 95 , 96 used device-based measures of PA, although only 2 included a comparison of PA levels. 73 , 95 Results from both studies were consistent with self- and proxy-report studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since sedentary children were found to present predominance of Th1 response in relation to active children, who instead showed higher levels of Interleukin 10 and higher regulatory T cell percentage, it could be hypothesized that regular PA may help to foster an anti-inflammatory profile. Consequently, prolonged social isolation during the COVID-19 pandemic, limiting PA, may lead to an increase in adiposity and susceptibility to inflammatory diseases ( 37 ).…”
Section: Decreased Physical Activity and Increased Sedentary Behaviors In Asthmatic Children And Its Impact During The Covid-19 Pandemicmentioning
confidence: 99%
“…All of which accumulate to increase the risk of chronic inflammatory diseases such as Alzheimer's disease and cardiovascular disease and allcause mortality (6)(7)(8)(9)(10). In humans, poor social connections result in an increased risk of depression (38)(39)(40) and anxiety which can lead to a cascade of poor lifestyle choices including a sedentary lifestyle, increased drinking, smoking and poor diet (41)(42)(43)(44)(45) and cause further withdrawal from society (11). This is clearly a vicious cycle.…”
Section: Introductionmentioning
confidence: 99%